(3GdJMQjGJ hQbGHI GdbVGA aj GdfXe GdebGQfI eY EWdGdI Ydi GdfXGe GdbVGFj GdEfLdjRj (B/s - (3SdjeGf, CTQa EHQGgje eUWais ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI,s, 2015)
(3jJMOK gPG GdcJGH Yf GdJMQjGJ hQbGHI GdbVGA Cf GdJMQjGJ gj GdhSjdI GdCSGSjI defY GdLQjeI bHd MOhKgG hGdcTa YfgG HYO MOhKgG agj JYJHQ GdSfO GdPi JYeO Edjg CLgRI GdVHW GdEOGQi ai GdeLJeY aj EWGQ GdeMGaXI Ydi GdMjGI GdYGeI hPdc HeYRd Yf GdJYOi Ydi MQjGJ hMbhb GdCaQGO Ef GdJMQjGJ hcjajI COGFgG hMOhOgG heLGdGJgG ef GdehVhYGJ GdTGFcI hGdMSGSI agd JSJWjY LgGJ GdVHW GdehGAeI Hjf MeGjI GdfXGe GdYGe hcPdc GdMaGX Ydi Mbhb GdehGWf(B.s
(3HHdjhLQGajI (B: (3UaMI (B355-366.s
Keywords: (3GdQbGHI GdbVGFjIs -- (3eUQs; (3GdVHW GdEOGQjs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdbQGQGJ GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs